2011
DOI: 10.1111/j.1365-2966.2011.19719.x
|View full text |Cite
|
Sign up to set email alerts
|

Two close large quasar groups of size ∼ 350 Mpc at

Abstract: The Clowes & Campusano large quasar group (LQG) atz = 1.28 has been re-examined using the quasar data from the DR7QSO catalogue of the Sloan Digital Sky Survey. In the 1991 discovery, the LQG impinged on the northern, southern and eastern limits of the survey. In the DR7QSO data, the western, northern and southern boundaries of the LQG remain essentially the same, but an extension eastwards of ∼2 • is indicated. In the DR7QSO data, the LQG has 34 members, withz = 1.28. A new group of 38 members is indicated at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(95 citation statements)
references
References 48 publications
1
94
0
Order By: Relevance
“…Haines, Campusano & Clowes (2004) reported the finding of two large-scale structures of galaxies in a 40 × 35 arcmin 2 field embedded in a 25 •2 area containing two 100 Mpcscale structures of quasars. As the identified scales of quasar clusters became larger, Clowes et al (2012) found two relatively close LQGs at z ∼ 1.2. The characteristic sizes of these two LQGs, ≈ 350 − 400 Mpc, and appear to be only marginally consistent with the scale of homogeneity in the concordance cosmology.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Haines, Campusano & Clowes (2004) reported the finding of two large-scale structures of galaxies in a 40 × 35 arcmin 2 field embedded in a 25 •2 area containing two 100 Mpcscale structures of quasars. As the identified scales of quasar clusters became larger, Clowes et al (2012) found two relatively close LQGs at z ∼ 1.2. The characteristic sizes of these two LQGs, ≈ 350 − 400 Mpc, and appear to be only marginally consistent with the scale of homogeneity in the concordance cosmology.…”
Section: Introductionmentioning
confidence: 96%
“…Until recently, this was the largest known structure in the Universe. Using a friend of friend (FoF) algorithm Einasto et al (2014) found that the linking length l = 70 h −1 M pc three systems from their QSR catalogue coincide with the LQGs from Clowes et al (2012Clowes et al ( , 2013. Horváth, Hakkila & Bagoly (2013); Horváth, Hakkila & Bagoly (2014) announced the discovery of a larger Universal structure than the Huge-LQG by analyzing the spatial distribution of gamma-ray bursts (GRBs).…”
Section: Introductionmentioning
confidence: 99%
“…From this catalogue, we select a subsample of quasars in the redshift interval 1.0 ≤ z ≤ 1.8 and apply an i-magnitude limit i = 19.1. The full quasar catalogue by Schneider et al (2010) is not homogeneous; Vanden Berk et al (2005) and Richards et al (2006) (see also Clowes et al 2012) gave a detailed analysis of the completeness of the sample and suggested to use these selection limits for statistical studies. To reduce the edge effects of our analysis, we limit the data in the area of SDSS sky coordinate limits −55 ≤ λ ≤ 55 degrees and −33 ≤ η ≤ 35 degrees.…”
Section: Datamentioning
confidence: 99%
“…We choose this redshift range as we are interested in the study of the cosmic web at high redshifts. This redshift range was also used by Clowes et al (2012Clowes et al ( , 2013; with this choice, we can compare LQGs found in these studies and our systems. We shall use the Schneider et al (2010) catalogue of quasars based on the Sloan Digital Sky Survey Data Release 7 (SDSS DR7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation